Effect of music therapy on heart rate variability in generalized anxiety disorder: A poincaré analysis - Mallik, Bithi; Ferdousi, Sultana; Sultana, Shamima (Journal of Bangladesh Society of Physiologist, 2020)
Background: Poincare plot analysis of heart rate variability (HRV) is a complex nonlinear method for assessing cardiac autonomic nerve function (CANF) in generalized anxiety disorder (GAD). Objective: This study aimed to observe the effect of music therapy on HRV by poincaré plot analysis in GAD patients. Methods: This prospective Interventional study was done in 2019 on 60 newly diagnosed GAD patients aged 20- 40 years, both male and female. Among them, 30 patients were under music therapy with Raga Bhairabi based Rabindra Sangeet for 3 months and 30 patients were without music therapy and both patient groups were studied over three months. Healthy controls, who were enrolled in this study, were Age, sex and BMI matched. Poincaré plot (non linear measure) of HRV of all GAD patients and control were recorded at baseline and after three months of follow up. HRV were recorded by Power Lab 8/ 35. For statistical analysis Bonferroni’s Post Hoc test and paired sample ‘t’ test were done. Results:Standard deviation of the points perpendicular to the axis of line of identity(SD1), standard deviation of the points along the axis of line of identity (SD2) SD and SD1/SD2 were significantly lower in all GAD patients compared to healthy control at baseline. After 3 months of music therapy, significant increment of these parameters occurred in GAD patients, whereas no changes of these except SD1 were noted in patients without music therapy after 3 months. Moreover, these parameters were not significantly different in patients under music therapy compared to control at the end of three months. Conclusion: This study concluded that music therapy can improve cardiac autonomic dysfunction in GAD patients. J Bangladesh Soc Physiol. 2020, June; 15(1): 39-45